Is the Adams D-15 colour vision test a sensitive screening tool for ethambutol- and linezolid-induced optic neuropathy? A retrospective case series - Van der Merwe, Pieter Jacobus Stephanus (Division of General Surgery, 2022)
Background: Ethambutol hydrochloride and linezolid are commonly used anti-tuberculous agents. Both agents can cause potentially blinding toxic optic neuropathy. Currently there is no low-cost, sensitive screening tool to detect early toxicity before permanent vision loss has occurred. Purpose: To evaluate the ability of the Adams D-15 colour vision test to detect early ethambutol- and linezolid-induced optic neuropathy. Methods: This was a retrospective case series of 15 patients who were screened for ethambutol- and linezolid-induced toxic optic neuropathy. At screening and follow-up visits, a detailed clinical history was taken, a standard of care examination performed and a battery of side-room investigations conducted, including: Farnsworth Munsell D15 (FM D15) and Adams D15 colour vision tests, retinal nerve fiber layer optical coherence tomography (RNFL-OCT) and a Humphrey visual field 24-2 (HVF 24-2). According to the results of these tests, the patients were classified into 3 groups: “No toxicity”, “Uncertain toxicity” or “Confirmed toxicity”. Results: Six patients were classified as “No toxicity”, 3 were “Uncertain toxicity” and 6 were classified as “Confirmed toxicity”. The Adams D15 showed a sensitivity of 100% for detecting a toxic optic neuropathy. Conclusion: The Adams D15 is a sensitive screening tool for the detection of early ethambutol- and linezolid-induced optic neuropathy.